2011
DOI: 10.1248/cpb.59.1163
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Component Organic and Glycosidic Acids of Crude Resin Glycoside Fraction from Calystegia soldanella

Abstract: NoteCalystegia soldanella ROEM. et SCHULT. (Convolvulaceae) is widely distributed on temperate sandy beaches of seas and lakes. The root of this plant is used for the treatment of arthritis.1) The isolation and structural elucidation were reported for two genuine resin glycosides, soldanellines A and B, as chemical constituents of the root.2,3) Prior to reinvestigation of the genuine resin glycosides of this plant, we examined the chemical components of the crude resin glycoside fraction of the leaves, stems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…2) In order to clarify the positions of the ester linkages, the 1 H-NMR signals due to the sugar moiety of 1 were assigned on the basis of 1 H-1 H correlation spectroscopy (COSY), heteronuclear multiple quantum coherence (HMQC), and heteronuclear multiple bond correlation (HMBC) spectra (Tables 1, 2). By comparing the chemical shifts of the 1 H-NMR signals between 1 and 5a, 2) the downfield shifts (Δδ= δ1-δ5a) due to acylation were observed for signals assignable to H-2 (Δδ= 1.21) and H-4 (Δδ= 1.46) of the rhamnosyl residue (Rha) and H-2 (Δδ=ca. 1.61) of the second glucosyl residue (Glc′).…”
Section: Calystegia Soldanella Roem Et Schult (Convolvulaceae)mentioning
confidence: 99%
“…2) In order to clarify the positions of the ester linkages, the 1 H-NMR signals due to the sugar moiety of 1 were assigned on the basis of 1 H-1 H correlation spectroscopy (COSY), heteronuclear multiple quantum coherence (HMQC), and heteronuclear multiple bond correlation (HMBC) spectra (Tables 1, 2). By comparing the chemical shifts of the 1 H-NMR signals between 1 and 5a, 2) the downfield shifts (Δδ= δ1-δ5a) due to acylation were observed for signals assignable to H-2 (Δδ= 1.21) and H-4 (Δδ= 1.46) of the rhamnosyl residue (Rha) and H-2 (Δδ=ca. 1.61) of the second glucosyl residue (Glc′).…”
Section: Calystegia Soldanella Roem Et Schult (Convolvulaceae)mentioning
confidence: 99%
“…The 1 H-and 13 C-NMR spectra indicated that 2 is composed of 1 mol each of tiglic acid and 6 and 2 mol of 2-methylbutyric acid (Tables 1, 2 2) showed acylation shifts (Δδ= δ2-δ6a) of signals due to H-2 (Δδ= 0.95) and H-4 (Δδ= 1.46) of Rha and H-2 (Δδ=ca. 1.51) and H-3 (Δδ=ca.…”
mentioning
confidence: 99%
“…The obtained extract was suspended in H 2 O and then extracted successively with ethyl acetate and n-butanol. The ethyl acetate-soluble fraction was subjected to silica gel column chromatography and HPLC on octadecyl silica (ODS) and naphthylethyl group bonded silica to yield five resin glycosides (1)(2)(3)(4)(5). H-NMR spectrum with that of an authentic sample.…”
mentioning
confidence: 99%
See 2 more Smart Citations